Impact of preoperative serum albumin on 30-day mortality following surgery for colorectal cancer: a population-based cohort study. Issue 1 (31st December 2015) - Montomoli, Jonathan; Erichsen, Rune; Antonsen, Sussie; Nilsson, Tove; Sørensen, Henrik Toft
Abstract : Objective: Surgery is the only potentially curable treatment for colorectal cancer (CRC), but it is hampered by high mortality. Human serum albumin (HSA) below 35 g/L is associated with poor overall prognosis in patients with CRC, but evidence regarding the impact on postoperative mortality is sparse. Methods: We performed a population-based cohort study including patients undergoing CRC surgery in North and Central Denmark (1997–2011). We categorised patients according to HSA concentration measured 1–30 days prior to surgery date. We used the Kaplan-Meier method to compute 30-day mortality and Cox regression model to compute HRs as measures of the relative risk of death, controlling for potential confounders. We further stratified patients by preoperative conditions, including cancer stage, comorbidity level, and C reactive protein concentration. Results: Of the 9339 patients undergoing first-time CRC surgery with preoperative HSA measurement, 26.4% (n=2464) had HSA below 35 g/L. 30-day mortality increased from 4.9% among patients with HSA 36–40 g/L to 26.9% among patients with HSA equal to or below 25 g/L, compared with 2.0% among patients with HSA above 40 g/L. The corresponding adjusted HRs increased from 1.75 (95% CI 1.25 to 2.45) among patients with HSA 36–40 g/L to 7.59 (95% CI 4.95 to 11.64) among patients with HSA equal to or below 25 g/L, compared with patients with HSA above 40 g/L. The negative impact associated with a decrement of HSA was found in all subgroups. Conclusions: A decrement in preoperative HSA concentration was associated with substantial concentration-dependent increased 30-day mortality following CRC surgery.